2021
DOI: 10.2147/jir.s323026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Virus Replication, Pathogenesis, and Cytokine Responses in Syrian Hamsters Inoculated with SARS-CoV-2

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus which caused a global respiratory disease pandemic beginning in December 2019. Understanding the pathogenesis of infection and the immune responses in a SARS-CoV-2-infected animal model is urgently needed for vaccine development. Methods Syrian hamsters ( Mesocricetus auratus ) were intranasally inoculated with 10 5 , 5×10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
5
16
0
Order By: Relevance
“…Consistent with a previous study, the main symptom of intranasal SARS-CoV-2 infection in Syrian hamsters was weight loss and recovery without obvious sequelae ( 8 10 , 14 ). Our data demonstrated that weight change can be separated into two stages, namely, the acute onset of rapid weight loss and the recovery course of gradual weight recovery.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with a previous study, the main symptom of intranasal SARS-CoV-2 infection in Syrian hamsters was weight loss and recovery without obvious sequelae ( 8 10 , 14 ). Our data demonstrated that weight change can be separated into two stages, namely, the acute onset of rapid weight loss and the recovery course of gradual weight recovery.…”
Section: Discussionsupporting
confidence: 90%
“…Abnormal liver function was a significant observation in patients with COVID-19 ( 20 , 21 ). A previous study on infected hamsters found that the AST/ALT ratio increased at acute onset, accompanied by structural abnormalities and large vacuoles in the liver ( 14 ). However, we found that the AST of the infection group increased slightly during the long-term monitoring, compared with that of the control group, while other hepatitis-related indicators did not change significantly.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is a limitation of the hamster model as it would not be useful to study the extrapulmonary pathologies that are observed in patients associated with COVID-19. Yang et al. (2021) recently used the Syrian hamster model to explore biomarkers of COVID-19.…”
Section: Animal Models Of Covid 19mentioning
confidence: 99%